2009
DOI: 10.1063/1.3274680
|View full text |Cite
|
Sign up to set email alerts
|

Recombination of polaron and exciton in conjugated polymers

Abstract: Both polarons and excitons, which are composite particles with internal lattice structure, play an important role in the transport and light-emitting properties of conjugated polymers for the use in, e.g., polymer based light-emitting diodes (LEDs). The scattering and recombination processes between a triplet exciton and a polaron are investigated using a nonadiabatic evolution method based on an extended Su-Schrieffer-Heeger model including interchain interactions. The results show that an excited polaron sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 33 publications
0
35
0
Order By: Relevance
“…18,30 The process is similar to the trion; recombination leads to an excited free polaron with a higher mobility. However, unlike the trion process, the two pair partners are weakly spin coupled.…”
Section: Triplet-exciton Polaron (Tep)mentioning
confidence: 97%
“…18,30 The process is similar to the trion; recombination leads to an excited free polaron with a higher mobility. However, unlike the trion process, the two pair partners are weakly spin coupled.…”
Section: Triplet-exciton Polaron (Tep)mentioning
confidence: 97%
“…[15][16][17][18][19][20] The effect of a magnetic field on these reactions was already considered by Ern and Merrifield in molecular crystals. 15 Desai et al 3 were the first to qualitatively describe how this can give rise to large room-temperature MC in disordered organic semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…8 The results showed that a bipolaron and an exciton can react with the production of a polaron and an excited polaron. Very recently, Li et al 9 and Meng et al 10 theoretically investigated the collision process between a polaron and a TE. a) Electronic mail: zhesu@ifm.liu.se.…”
Section: Introductionmentioning
confidence: 99%